Integrasi Materi Eksponen pada Surah Al-Ikhlas dalam Pembelajaran Matematika - Surani, Nur Eka; Sholihah, Futuha Rohmatish; Al Hakim, M. faris; Risdiana, Syakirna Shifa; Kholil, Mohammad (Radian Journal: Research and Review in Mathematics Education, 2023)
The monotheism value contained in the surah is in the holy book of the Al-Quran, especially in sura Al-Ikhlas. In surah Al-Ikhlas this can be related to exponential material. The purpose of this research is to find out whether there is a relationship between exponential material and surah Al-Ikhlas. Thus, the integration of mathematics and monotheism can help us to gain a broader and deeper understanding of mathematical concepts. The method used in this study is a literature review. The results of this study are (1) The first verse in surah Al-Ikhlas which contains "Say O Muhammad, He is Allah, the One and Only". Similar to the concept of the oneness of Allah, that Allah is one and is not divided into several gods. (2) The second verse in surah Al-Ikhlas states "Allah is the place of asking (place of dependence) of everything". The concept of dependency contained in this paragraph can be connected with the concept of exponential as a power operation. (3) The third verse in surah Al-Ikhlas states “Neither begotten nor begotten”. The concept of childlessness and non-producing in this verse can be related to the concept of exponents which relates to the power of zero. This is similar to the concept that Allah is not begotten and not beget